AGAMA DAN KONFLIK SOSIAL - Rahmat, Stephanus Turibius (STKIP Santu Paulus Ruteng, 2016)
Abstract: Religion and Social Conflict. Every religion is present as a carrier of love and peace institution for the adherent of that religion. Even though, religion is often regarded as the cause of various social conflict that occur. Religious sentiment is often used for the interest of a groups or certain parties. Religion loses power as a source of spiritual inspiration for each adherent. Therefore, we need to find a new paradigm of religious life and religious position in accordance with the vision and its fundamental mission. All religion need to continously foster the spirit of tolerance within each adherent, doing constructive interreligious dialogue, as well as striving for peace without violence (non-violence). Thus, religion can appear as an institution that teaches the truth and true peace. Keywords: religion, social conflict Abstrak: Agama dan Konflik Sosial. Setiap agama hadir sebagai institusi pembawa cinta dan damai bagi para penganutnya. Walaupun demikian, agama sering diredusir sebagai penyebab dari pelbagai konflik sosial yang terjadi. Sentimen agama sering digunakan untuk kepentingan kelompok atau pihak-pihak tertentu. Agama kehilangan daya sebagai sumber inspirasi rohani bagi para penganutnya. Oleh karena itu, kita perlu mencari paradigma baru hidup beragama dengan memposisikan agama sesuai dengan visi dan misi funtamentalnya. Semua agama perlu secara terus-menerus menumbuhkan semangat toleransi dalam diri setiap penganutnya, melakukan dialog antaragama yang bersifat konstruktif, serta memperjuangan perdamaian tanpa kekerasan. Dengan demikian, agama dapat tampil sebagai institusi yang mengajarkan kebenaran dan kedamaian yang sejati. Kata kunci: agama, konflik sosial